PERBEDAAN KEBOCORAN MIKRO ANTARA TUMPATAN RESIN KOMPOSIT NANOHIBRID KONVENSIONAL DAN NANOHIBRID FLOWABLE - , MULYANI; , drg. Ema Mulyawati, MS., Sp.KG(K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Despite extensive researches resulted in significant improvements in the clinical performance of resin-based restorative materials, microleakage remains a persistent handicap. In recently, composite resin are developing and a resolution introduced are nanohybrid conventional and nanohybrid flowable. With nano particles are expected to decrease the microleakage. The aim of this study was to determine the difference microleakge between conventional nanohybrid composit resin and flowable nanohybrid composite resin. This study 20 subjects were used, divided into two groups: Group I conventional nanohybrid composite resin and Group II flowable nanohybrid composite resin.The first and second premolar teeth were prepared on the buccal surface of cavities of V class, with diameter of 2 mm and 2 mm depth. Conventional nanohybrid composite resin and flowable nanohybrid with a thickness of 2 mm in the cavity and curing for 40 seconds. All soaked in pH 6.8 artificial saliva for 24 hours and is performed using thermocycling waterbath. Furthermore, the teeth coated with nail polish and sticky wax and immersed in a solution of 2% methylene blue for 24 hours. Teeth were divided into two directions bukopalatal and observed under a stereo microscope with a magnification of 20x. Data analysis using the Mann-Whitney test. The results showed a significant differences between the microleakage of conventional nanohybrid composite resin and flowable nanohybrid composite resin restorations (p <0.05). Levels of microleakage in flowable nanohybrid composite resin is greater than the conventional (p = 0.009).